Psychological aspects of prolonged headdown bed rest in healthy male subjects - Petra Dolenc; Tjaša Dimec; Matej Tušak; Rado Pišot (Exercise and Quality of Life)
The aim of the study was to examine the effects of head-down bed rest on psychological well-being in young healthy subjects. Head-down tilting bed rest (BR) is a well-accepted method by which to simulate an acute stage of human adaptation to the microgravity in space flights and also an important model to study consequences of physical inactivity and sedentarism on human body. The subject participating in the study were ten healthy males aged between 20 and 30 who were exposed to a 35-day strict rest in hospital environment. The participants were asked to complete psychometrical inventories – General Health Questionnaire, Satisfaction with Life Scale, State Anxiety Inventory, Center for Epidemiological Studies Depression Scale and Emotional States Questionnaire – on before and after the BR experiment. There were no significant differences in examined psychological variables between pre and post BR period. Research results do not show any adverse effects of a prolonged physical inactivity on perception of health and psychological well-being of selected group of subjects. The importance of this research was to provide evidence that the provision of favourable habitability countermeasures can prevent deterioration in the psychological state under conditions of physical immobilisation. Our findings applied value in the field of health prevention and rehabilitaion. Research of psychological and cognitive aspects within bed rest studies deserves special attention and consideration in the future. Psychic balance and emotional strength have undoubtedly an important role in reducing the consequences of physical impairment and physiological changes due to prolonged bed rest.